APLIKASI TEKNIK PROBIOTIK TERHADAP KUALITAS AIR MEDIA BUDIDAYA IKAN LELE SANGKURIANG (Clarias gariepinus) DI DESA TAMBAKSARI, KECAMATAN ROWOSARI, KABUPATEN KENDAL - Diana Rachmawati; Istiyanto Samidjan; Slamet Budi Prayitno (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
Application of probiotic technology is done to maintain water quality of aquaculture media of Sangkuriang catfish in Tambak Sari Village, Rowosari District, Kendal Regency. The aims of this study was to determine the effect of probiotic on water quality of Sangkuriang catfish cultivation medium in Tambak Sari Village. Sangkuriang catfish with age 15 days is material used in this study. Sangkuriang catfish kept for 45 days. The results showed there was a difference in the increase of body length and weight of Sangkuriang catfish on the culture medium with the application of probiotics and unprobiotics. media aquculture of applying probiotic techniques showed better and more feasible conditions for the cultivation of the Sangkuriang catfish.Key word : Sangkuriang catfish, aquaculture, probiotic